EFEKTIVITAS LKS BERBASIS PENDEKATAN OPEN-ENDED TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Nur Fitriyana; Lucy Asri Purwasi (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to determine the effectiveness of worksheets based on an open-ended approach to students' mathematical problem solving abilities. Subjects in the study were eighth grade public and private junior high school students in Lubuklinggau City who were from 3 schools. Each school is SMP Negeri 1 Lubuklinggau totaling 33 students, SMP Negeri 14 Lubuklinggau totaling 29 students and SMP PGRI 3 Lubuklinggau totaling 14 students. Data collection techniques in this study are test techniques. the test used in the study is a description test which is compiled based on indicators of mathematical problem solving abilities. The data analysis technique used in this study is one sample t-test with the help of SPSS Version 24 program.The data analysis t-test students' mathematical problem solving capabilities of three schools only SMP Negeri 1 Lubuklinggau which show significantly less than equal to 61 (μo 61). SMP Negeri 14 Kota Lubuklinggau and SMP PGRI 3 Lubuklinggau showed that the average mathematical problem-solving ability of students after using LKS based on open-ended was significantly more than 61 (μo 61). Of the two schools that have been represented, it can be concluded that the implementation of Open-ended worksheets is effective to use.This study aims to determine the effectiveness of worksheets based on an open-ended approach to students' mathematical problem solving abilities. Subjects in the study were eighth grade public and private junior high school students in Lubuklinggau City who were from 3 schools. Each school is SMP Negeri 1 Lubuklinggau totaling 33 students, SMP Negeri 14 Lubuklinggau totaling 29 students and SMP PGRI 3 Lubuklinggau totaling 14 students. Data collection techniques in this study are test techniques. the test used in the study is a description test which is compiled based on indicators of mathematical problem solving abilities. The data analysis technique used in this study is one sample t-test with the help of SPSS Version 24 program.The data analysis t-test students' mathematical problem solving capabilities of three schools only SMP Negeri 1 Lubuklinggau which show significantly less than equal to 61 (μo 61). SMP Negeri 14 Kota Lubuklinggau and SMP PGRI 3 Lubuklinggau showed that the average mathematical problem-solving ability of students after using LKS based on open-ended was significantly more than 61 (μo 61). Of the two schools that have been represented, it can be concluded that the implementation of Open-ended worksheets is effective to use.